Interplay between cross sectional analysis of risk factors associated with Toxoplasma gondii infection in pregnant women and their domestic cats - Hassanen, Eman A. A.; Makau, Dennis N.; Afifi, Mohamed; Al-Jabr, Omar A.; Abdulrahman Alshahrani, Mohammed; Saif, Ahmed; Anter, Reham G. A.; El-Neshwy, Wafaa M.; Ibrahim, Doaa; Abou Elez, Rasha M. M. (Frontiers in Veterinary Science, 2023)
Toxoplasmosis is a global zoonotic disease caused by Toxoplasma gondii (T. gondii). The primary aim of this study was to identify hygienic and cat management practices that could affect the occurrence of T. gondii in cats and their owners in Sharqia Governorate, Egypt. T. gondii infection was evaluated in 80 pregnant women and 29 domestic cats using Real-time PCR. A questionnaire was administered to obtain information regarding the risk factors associated with T. gondii infection. Blood samples were collected from enrolled pregnant women, and faecal samples were collected from their pet cats. Firth logistic regression model complemented with random forest (RF) analysis was used to evaluate the association of different hygiene and cat management practices with T. gondii infection in pregnant women. T. gondii infection was identified in 27.5% of pregnant women and 17% of domestic cats. Drinking raw milk and contacting stray and pet cats were significantly associated with higher odds of T. gondii infection. The proportion of T. gondii-positive women who ate raw meat (60.0%) was higher than those who ate heat-cocked meat (25.3%). Moreover, women who did not wash their hands after contact with cats were 6 times (OR 6.12; CI: 3.03 - 9.21) more likely to experience T. gondii infection than those who washed their hands after cat contact. The RF analysis showed that. Washing hands constitute a serious yet preventable public health concern that requires targeted, community-specific efforts. Public health agencies could consider findings in developing messaging, particularly as we highlighted.